Analisis Pemanfaatan Sewa Aset Daerah dalam Upaya Mempertahankan Opini WTP atas LKPD Provinsi Jawa Barat - Cica Purnamasari; Mia Rosmiati; Neneng Dahtiah (Indonesian Accounting Research Journal, 2021)
The West Java Provincial Government has received WTP opinion 9 times since 2011. However, asset issues are still a finding, including the utilization of regional asset leases. This research aims to analyze procedures and problems of the use of regional asset leases, and to know the efforts of the West Java Provincial Government in overcoming these problems. The research method used is qualitative research method with descriptive analysis approach, with data collection techniques are interviews, observations and documentation. The results showed that the utilization of regional asset leases in the Regional Government of West Java Province was guided by Permendagri Number 19 of 2016 and West Java Regulation No. 46 of 2017. Problems in the implementation of the use of regional asset leases are the signing bureaucracy of the approval and lease agreement, applicable regulations, determination of rental rates and lease renewal times, and land disputes. The government's efforts to address this problem are revise regulations, socialize government assets, safeguard assets and carry out administrative order.